Biochar innovations for sustainable agriculture: Acidification and zinc enrichment strategies to improve calcareous soil fertility and wheat yield - Demirkaya, Salih; Gülser, Coskun (Soil and water research, 2025)
Calcareous soils, typically characterized by low fertility, low organic matter and nitrogen content, and often deficient in phosphorus, zinc, and iron, as well as having low microbial activity, require the development of sustainable soil conditioners to improve fertility. To address these shortcomings and promote sustainable agriculture, biochar, especially with acidic character, may offer a promising solution. This study investigates the effects of modified biochar by H2SO4 and ZnSO4on soil properties and wheat yield under field conditions. For this purpose, biochar (B), acidified biochar (AB), Zn enriched biochar (BZn), and acidified-Zn enriched biochar (ABZn) were applied to the field at two different doses (0.5 and 1.0%) together with the control treatment (Ck) without biochar application. AB1.0% was determined as the most effective treatment in decreasing soil pH (0.15 units), while B1.0% was determined as the most effective treatment in increasing organic carbon and cation exchange capacity, 13% and 32%, respectively. The effect of the treatments varied for specific nutrients. The highest antioxidant enzyme activities were found in acidified biochars where the lowest yields were obtained. Compared to the Ck, the highest catalase (CAT) (32%) was determined in ABZn1.0%, ascorbate peroxidase (APX) (56%) and glutathione peroxidase (GPX) (36%) were determined in ABZn0.5%, and superoxide dismutase (SOD) (28%) was determined in AB0.5%. The highest proline (PRO), with the least decrease in yield, was found in the AB1.0% application, which is 205% more than Ck. B and BZn treatments all increased the grain yield, and the highest increase was 20% in B1.0%when compared to the Ck.